Curricoli digitali Nuove intelligenze, nuovi diritti - RIVOLTELLA, Pier Cesare; Villa, Adelaide; BRUNI, Filippo (Media e tecnologie per la didattica, 2023)
The present volume provides documentary evidence of the project "Internet Rights: towards a Digital Citizenship", which began in 2016 through a ministerial announcement and ended in June 2022. In the project collaborated the following institutions: I) a network formed by schools from Molise, whose leader was the technical institute "G. Marconi" of Campobasso; II) the University of Molise; III) CREMIT - Media, Innovation and Technology Education Research Centre, Catholic University of the Sacred Heart, Milan; IV) the social cooperative EDI Onlus - Childhood and Adolescence Rights Education Onlus. The outcome of the project represents a digital framework with which students will acquire skills necessary to exercise their Internet Rights. The volume and the specific cards available in it and on the website represent a useful and tangible tool for teachers to design and manage new courses and laboratories in middle and high schools.